Changes in SOFC Cathode Crystallographic Structure Induced by Oxygen Deficiency in Cathode Room. (30th May 2017) - Kivi, Indrek; Aruväli, Jaan; Nurk, Gunnar; Lust, Enn
Abstract : Porous and monolithic La0.6 Sr0.4 CoO3 −δ, Gd0.15 Sr0.85 CoO3 −δ and La0.6 Sr0.4 MnO3 −δ cathodes for intermediate temperature solid oxide fuel cell applications have been studied at different cathode potentials and at different oxygen partial pressures using high-temperature in situ XRD (HT-XRD) method. The kinetic response of the crystallographic structure and lattice parameters on the changes of electrode potential has been correlated with the electrochemical measurement data and discussed. Reversible changes in the lattice parameters were observed depending on the temperature ( T ), electrode potential ( E ) and oxygen partial pressure ( p O2 ) applied. At fixed T and electrode potential the oxygen partial pressure remarkably influences the unit cell volume, which is very sensible with the electrode microstructure and porosity as well as electrode chemical composition.